The Influence of Size in Augmented Reality Telepresence Avatars - Walker, Michael E.; Szafir, Daniel; Rae, Irene (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
In this work, we explore how advances in augmented reality technologies are creating a new design space for long-distance telepresence communication through virtual avatars. Studies have shown that the relative size of a speaker has a significant impact on many aspects of human communication including perceived dominance and persuasiveness. Our system synchronizes the body pose of a remote user with a realistic, virtual human avatar visible to a local user wearing an augmented reality head-mounted display. We conducted a two-by-two (relative system size: equivalent vs. small; leader vs. follower), between participants study (N = 40) to investigate the effect of avatar size on the interactions between remote and local user. We found the equal-sized avatars to be significantly more influential than the small-sized avatars and that the small avatars commanded significantly less attention than the equal-sized avatars. Additionally, we found the assigned leadership role to significantly impact participant subjective satisfaction of the task outcome.